Boston carpal tunnel syndrome questionnaire clinical function assessment outcomes of carpal tunnel injection for carpal tunnel syndrome - Nasution, Nino; Benny; Fitriadi, Didi (International Surgery Journal, 2024)
Carpal tunnel syndrome is the most common compressive neuropathy. Risk factors include hereditary, obesity, pregnancy, hypothyroidism, rheumatoid arthritis, and work related. With treatment ranging from simple lifestyle changes, up until surgery. Studies have shown that local steroid injection improve symptoms by at least one month and up to one year after injection, which allows for the delay of surgical treatment. In this study, BCTQ was chosen as a measuring tool because it can objectively assess functional improvement in functional status and disease severity. An analytical study design with a quasi-experimental pretest post-test one group only design approach was used in this study. Primary data and secondary data were used to measure the symptom severity scale and functional status based on the BCTQ. The research subjects were taken from populations that fulfilled the inclusion and exclusion criteria. Based on the Friedman test analysis of differences in the severity scale of symptoms of clinical function assessment outcome data and functional status on the BCTQ from the action of carpal tunnel injection on carpal tunnel syndrome, the results of the BCTQ value show that there is a significant difference before and after injection at one month and three months assessment post injection with a P-value of 0.00 (p<0.05) on both. Carpal tunnel injection with Triamcinolone acetonide 20 mg can provide good clinical outcomes in cases of carpal tunnel syndrome and can reduce the severity of symptoms and provide a good functional status scale of the hand.